2010
DOI: 10.3201/eid1611.100703
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 3 Infrared Thermal Detection Systems and Self-Report for Mass Fever Screening

Abstract: In a hospital setting, the systems had reasonable utility for fever detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
4
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(105 citation statements)
references
References 34 publications
6
89
4
2
Order By: Relevance
“…These differences in results may be based on a number of influencing factors such as the data collection time, room temperature (Ammer & Ring, 2008), type of camera used (Nguyen et al, 2010) and race of the subject (Zhu and Xin, 1999). For a better comparison of data in future studies, it is important to indicate the criteria and conditions for data collection and to identify the cameras used.…”
Section: Datamentioning
confidence: 99%
“…These differences in results may be based on a number of influencing factors such as the data collection time, room temperature (Ammer & Ring, 2008), type of camera used (Nguyen et al, 2010) and race of the subject (Zhu and Xin, 1999). For a better comparison of data in future studies, it is important to indicate the criteria and conditions for data collection and to identify the cameras used.…”
Section: Datamentioning
confidence: 99%
“…Initial studies testing IRT accuracy and practicability were undertaken for febrile patients evaluation. Results vary among series with some disappointing (13,14) and other promising reports (11,12). Our experiment showed excellent accuracy of the IRT compared to digital contact thermometer.…”
Section: Discussionmentioning
confidence: 99%
“…IRT infer temperature by using a portion of the thermal radiation emitted by the object of measurement. Its accuracy has been tested in several centers for evaluation of febrile patients and some authors found reliable results when compared to Infrared Thermometer: an accurate tool for temperature measurement during renal surgery _______________________________________________ standard mercury thermometer (11,12). Others could not obtain the same results and controversy persists (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…This technique is based on the polynomial fit of each pixel time history from the given thermographic image sequence. The evolution of the temperature is adjusted to an n degree polynomial for input value x, what described in equation [13]: …”
Section: Th International Conference Diagnostics Of Machines and Vehimentioning
confidence: 99%